Inflammatory bowel disease drastically affects the prognosis of patients treated for peritoneal metastases with combined cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: A multicenter study. Issue 6 (June 2018) - Hammoudi, Nassim; Eveno, Clarisse; Lambert, Jérôme; Maillet, Marianne; Glehen, Olivier; Goere, Diane; Lourenco, Nelson; Allez, Matthieu; Aparicio, Thomas; Pocard, Marc; Gornet, Jean-Marc; ,
Abstract: Background: Complete cytoreductive surgery (CCRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC) is a validated treatment in selected patients with peritoneal metastases (PM) of intestinal origin. There is an increased risk of Colorectal Cancer (CRC) and Small Bowel Adenocarcinoma (SBA) in Inflammatory Bowel Disease (IBD). The feasibility and benefit of that surgical approach in IBD patients is unknown. Methods: IBD patients with operated PM complicating CRC or SBA were extracted from a French national multicenter prospective database of patients who underwent surgery for PM in HIPEC expert centers from 1995 to 2016. IBD patients who underwent CCRS plus HIPEC were compared with a cohort of 234 patients who had the same surgery for sporadic colon cancer. Results: 14 patients (male 57%, median age 40 years, 12 Crohn's disease) with CRC (n = 7) and SBA (n = 7) were included. CCRS followed by HIPEC (oxaliplatin 72.7%) was performed in 11 cases (median peritoneal cancer index 7; range 1–30). The control group had the same characteristics except an older age at HIPEC (56.52 vs 45.74; p = 0.003). Overall survival (HR = 4.47; 90% CI, 1.91 to 10.49), Relapse Free Survival (HR = 2.31; 90% CI, 1.17 to 4.56) and Peritoneal Recurrence Free Survival (HR = 3.30; 90% CI, 1.59 to 6.85) were significantly lower in IBD patients. Six of the 11 patients presented major surgical morbidity with no impact on post-operative treatment. Conclusion: CCRS followed by HIPEC is less effective in IBD patients with resectable PM complicating CRC or SBA. More careful selection of those patients is needed.